IMPLEMENTATION OF MEDAN MAYOR REGULATION NUMBER 51 OF 2021 ON THE PERFORMANCE OF THE HEAD OF THE ENVIRONMENT IN KELURAHAN BESAR, MEDAN LABUHAN DISTRICT, MEDAN CITY - Nurmala Sari Harahap; Isnaini Isnaini; Maksum Syahri Lubis (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study analyzes the implementation of Medan Mayor Regulation Number 51 of 2021 in Kelurahan Besar, Medan Labuhan District, with a focus on the role of environmental heads in optimizing Land and Building Tax (PBB) revenue. Based on Edward III's policy implementation model, policy success is influenced by communication, resources, disposition (implementing attitude), and bureaucratic structure. This study employs a descriptive qualitative method, utilizing data collection techniques that include interviews, observations, and documentation of informants, comprising village heads, neighborhood heads, government section heads, and community members. The study's results indicate that the implementation of this policy still faces several obstacles, including the lack of systematic socialization, limited work facilities, low performance-based incentives, and a lack of coordination among agencies. In addition, low public tax awareness, mainly due to post-pandemic economic conditions, further worsens the effectiveness of policies. The solution includes technical guidelines, training, incentives, coordination, and performance evaluation to optimize Medan Mayor Regulation Number 51 of 2021 and increase Regional Original Revenue (PAD).